Osteolytic Bone Metastasis: Different Radiotherapy Fractionation Schedules Compared Clinically and Radiographically - Zoi Liakouli; Anna Zygogianni; Ioannis Georgakopoulos; Kyriaki Mystakidou; John Kouvaris; Christos Antypas; Maria Nikoloudi; Vasileios Kouloulias (Current Oncology, 2024)
The purpose of this study is to compare three commonly used radiotherapy fractionation schedules for bone metastasis in terms of clinical and radiological effectiveness. A total of 93 patients with osteolytic bone metastasis were randomized to receive 8 Gyin a single fraction (group A), 20 Gy in 5 fractions (group B) and 30 Gy in 10 fractions (group C). Changes in bone density were measured using the Relative Electron Density (RED) type corrected by Thomas (pe = HU/1.950 + 1.0), where HU is Hounsfield Units. Pain response was assessed according to the Brief Pain Inventory tool. Quality of life was estimated using the EORTC QLQ-C30 and the MD Anderson Symptom (MDAS) tools.After RT, RED, together with the parameters of EORTC QLQ-C30, MDAS and SAT, significantly increased in all groups (p < 0.001).Specifically, the increase of RED was higher in group C compared to group Athree months post-RT (p = 0.014). Group C was also superior to group A in terms of QoL and BPI three months post-treatment. Multifractionated radiotherapy for osteolytic bone metastasis is superior to single fraction radiotherapy in terms of improvement in quality of life and bone remineralization three months post-RT.